Material metabolism and lifecycle impact assessment towards sustainable resource management: A case study of the highway infrastructural system in Shandong Peninsula, China. (1st June 2017) - Guo, Zhen; Shi, Honghua; Zhang, Peidong; Chi, Yuan; Feng, Aiping
Abstract: The accelerated construction of general infrastructure with global urbanization necessitates the massive input of materials. The huge material input and waste output throughout the infrastructure's lifecycle have led to severe resource depletion and the accumulation of potential environmental risks. The systematic evaluation of typical infrastructure stocks is very important to study regional resource availability and explore sustainable development modes under intensive human activities. In this study, we build a material stock model for a highway system that is based on the theory of material metabolism. We analysed the scale and structures of the stock and its lifecycle effects in the Shandong Peninsula. The following results are shown: 1) the total material stock in the entire highway system was 1933.57 Mt in 2013, and the six materials with the largest inputs were stones, fly ash, lime, cement, mineral powder and asphalt, which together comprised 99.8% of the stocks; 2) the material-driven impacts mainly originated from production and construction stages, of which the main damage types were fossil fuels, inhalable inorganics, climate change and land use; 3) the end products for highway construction were mainly supplied by Shandong itself. The average transport distance for different materials ranged from 25 to 174 km. Steel, stone and asphalt had a longer transport distance than others; and 4) the top three parameters that largely affected the stocks were the road length, roadway structure, and cross-sectional subgrade structure. The inputs could be largely reduced by appropriately adjusting the structures of roadways and subgrades in low-class roads. Highlights: The intensive construction of highway infrastructure consumes massive resources. A model that is based on material metabolism is built to calculate the stock of highway systems. Great changes in the in-used stock occurred in 2003–2008 because of government policies. Raw material production is the stage with the greatest environmental impacts. Average transport distance for different construction materials (end products) ranged from 25 to 174 km.